A novel allele, HLA‐B*55:70 was identified in a Chinese cord blood donor. (26th February 2016) - Wang, W.; Chen, N.‐Y.; Dong, L.‐N.; He, J.; Zhu, F.‐M.
Abstract : HLA ‐B*55:70 has one base substitution at position 199 C>T in exon 2 compared to HLA ‐B*55:02:01.